2019
DOI: 10.1590/1678-7757-2018-0358
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-month clinical performance of different universal adhesives in etch-and-rinse, selective etching and self-etch application modes in NCCL – a randomized controlled clinical trial

Abstract: Objective The aim of this randomized, controlled, prospective clinical trial was to evaluate the performances of two different universal adhesives and one etch-rinse adhesive for restoration of non-carious cervical lesions (NCCLs). Material and Methods Twenty patients with at least seven NCCLs were enrolled. Lesions were divided into seven groups according to adhesive systems and application modes: GSE: GLUMA Universal-self-etch, GSL: GLUMA Universal-selective etching, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 34 publications
2
47
1
Order By: Relevance
“…The present study used Ambar Universal, using phosphoric acid only in enamel and applying the self-etching adhesive to dentin. This strategy is reported in the literature for showing good results over time, mainly for the post-operative sensitivity factor [28,29]. The ndings of the present study for this parameter are inconsistent with the recent study [26] who reported persistent sensitivity for one of the groups that used bulk-ll composite resin.…”
Section: Discussioncontrasting
confidence: 96%
“…The present study used Ambar Universal, using phosphoric acid only in enamel and applying the self-etching adhesive to dentin. This strategy is reported in the literature for showing good results over time, mainly for the post-operative sensitivity factor [28,29]. The ndings of the present study for this parameter are inconsistent with the recent study [26] who reported persistent sensitivity for one of the groups that used bulk-ll composite resin.…”
Section: Discussioncontrasting
confidence: 96%
“…A durable and lasting bond to tooth structure can be achieved most effectively using self-etch or universal adhesives with a selective etching technique because the effectiveness of acid etching on dentin still remains controversial. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have mentioned that resin-based composites and resin-modified glass ionomer cement are acceptable for restoring such defects [1,[25][26][27][28][29][30][31][32]. Resin-based composites are more strongly recommended due to their good bonding abilities, satisfactory tooth-colored appearance, and ease of manipulation [31,32]. However, we found no publication reporting the optimum depth of an NCCL for the restoration to prevent damage or the suitability of resin-based composites in inhibiting NCCL progression.…”
Section: Introductionmentioning
confidence: 99%